Expresión corporal: detonante de cambio de las interacciones en el espacio urbano (2019)
The article approaches the issue of pedestrian interactions in the public space of Bogotá, which are difficult due to various problems in the city. The theoretical framework of the article are two recurring concepts in the performing arts: the proxemics and the kinetic. The methodology is of qualitative type, and is based on the description of the phenomena and the object of study, to conclude with interpretive or hermeneutic exegesis process-es. The results are presented in three sections: public space; body expression and urban interactions. It is concluded that the technique of body expression can contribute to the improvement of urbanites’ interactions in the urbs public space.